Front Cover: Piezofluorochromism in Charge‐Transfer Inclusion Crystals: The Influence of High Pressure versus Mechanical Grinding (ChemPhotoChem 5/2018). Issue 5 (26th April 2018) - Ono, Toshikazu; Tsukiyama, Yoshifumi; Taema, Ai; Sato, Hiroyasu; Kiyooka, Hidetoshi; Yamaguchi, Yuma; Nagahashi, Ayumi; Nishiyama, Manami; Akahama, Yuichi; Ozawa, Yoshiki; Abe, Masaaki; Hisaeda, Yoshio
Abstract : The Front Cover illustrates the distinct piezochromic response of charge‐transfer inclusion crystals, which consist of small aromatic guest molecules with naphthalenediimide derivatives. Reversible multichromism is observed over the entire visible region in response to high pressure using a diamond anvil cell, whereas a weak response to mechanical grinding is evident. More information can be found in the Communication by T. Ono et al. onpage 416 in Issue 5, 2018 (DOI:10.1002/cptc.201700227 ).